Impact of Smoking and Drinking on Complications After Revision Total Joint Arthroplasty: A Matched Cohort Analysis. Issue 15 (1st August 2021) - Tirumala, Venkatsaiakhil; Bounajem, Georges; Klemt, Christian; Barghi, Ameen; Kwon, Young-Min
Abstract : Introduction: Smoking and drinking have been shown to impair postoperative outcomes in primary hip and knee total joint arthroplasty (TJA). This study aimed to evaluate the potential impact of smoking and drinking on complications after revision TJA. Methods: We retrospectively evaluated a total of 4, 302 consecutive patients who underwent revision TJA. Patient demographics and complications were compared between four cohorts based on smoking and drinking status: (1) nonusers (nonsmokers and nondrinkers), (2) smokers, (3) drinkers, and (4) concurrent users. Results: A total of 1, 924 patients were matched using propensity score analysis: 808 nonusers (42.0%), 421 smokers (21.9%), 483 drinkers (25.0%), and 212 concurrent users (11.1%). When compared with nonusers, smokers, drinkers, and concurrent users (simultaneous smokers and drinkers) exhibited higher odds for both inhospital complications (odds ratios, smokers: 2.40, drinkers: 1.55, and concurrent users: 5.13, P < 0.01). Among the user cohorts, although smokers and drinkers showed similar rates of 90-day postdischarge complications (smokers: 14.95% and drinkers: 14.80%, P = 0.95), concurrent users demonstrated the highest significant odds for these complications (odds ratio, 1.64, P = 0.02). Discussion: Our propensity-score-matched cohort study results demonstrate that although the smokers and drinkers groups shared similarly poor outcomes after discharge, concurrent users were found to have the worst outcomes compared with either single user group.